Population growth curve of Spodoptera frugiperda in maize in Irapuato, Guanajuato, Mexico - Martínez Jaime, Oscar Alejandro; Salas Araiza, Manuel Darío; Díaz García, José Antonio (Agronomía Mesoamericana, 2018)
The fall armyworm Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) is an important pest of maize (Zea mays L.) in Irapuato, Guanajuato, Mexico. The objective of the study was to obtain the population growth curve (and its estimation) of the adults of S. frugiperda in the maize crop in Irapuato, Guanajuato, Mexico. Applying the multiple regression technique, the functional form of a third-degree polynomial was obtained, in terms of temperature and precipitation, using the monthly averages available from 1993 to 2002. The estimated equation was: Y = 821.347 – 104.728T + 2.737P + 3.448T2 – 0.019P2 – 0.180TP + 0.001TP2 (1), where T was the average monthly mean temperature, P was the average monthly accumulated precipitation, and Y was the average of adults of S. frugiperda per month. In addition, using standard mathematical programming techniques, the critical temperature and the critical precipitation were calculated (T=13.70 °C, P=38.70 mm) obtaining the average of maximum number of individuals of this specie per month, which was 39 adults. The prediction model (1) provided information to reach deep understanding of the fluctuation of this species population, and contributed, therefore, to make the integrated pest management in maize crop more efficient, in the region of “El Bajío” of Guanajuato.